2003
DOI: 10.1046/j.1529-8027.2003.03016_4.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Neuropathy – I. Spatiotemporal Characteristics of Nerve Cell Damage in Rat Cerebellum

Abstract: Based on evidence from morphometric studies of PNS, we suggested that acrylamide (ACR)‐induced distal axon degeneration was a secondary effect related to duration of exposure (Toxicol Appl Pharmacol 151 [1998] 211). To test this hypothesis in CNS, the cupric‐silver stain method of de Olmos was used to define spatiotemporal characteristics of nerve somal, dendritic, axonal and terminal degeneration in rat cerebellum. Rats were exposed to ACR at either 50 mg/kg per day (i.p.) or 21 mg/kg per day (p.o.) and at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…10-50 mg/kg per day for 28 days), axon degeneration in PNS and CNS occurred only during long-term exposure to lower ACR doserates (e.g. 21 mg/kg per day for 42 days) [6] . The dissociation between neurological dysfunction and the presumed underlying morphological lesion suggests that axonopathy might not be importantly involved in the pathophysiological process leading to ACR neurotoxicity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…10-50 mg/kg per day for 28 days), axon degeneration in PNS and CNS occurred only during long-term exposure to lower ACR doserates (e.g. 21 mg/kg per day for 42 days) [6] . The dissociation between neurological dysfunction and the presumed underlying morphological lesion suggests that axonopathy might not be importantly involved in the pathophysiological process leading to ACR neurotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Completed morphological studies [6] using a contemporary amino-cupric silver staining method to detect degenerating neurons and their processes indicated that intoxication at a higher ACR dose-rate produced selective, widespread degeneration of nerve terminals in rat brain and spinal cord regions. Intoxication at a lower dose rate was associated with initial nerve terminal degeneration followed later by pre-terminal axon degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Evidences suggested that the neurotoxicity produced by A exposure is linked to nerve terminal damage in the central and peripheral nervous system which is mediated by injury to nerve terminals and cerebellar purkinje cells. 29,32 KPF is a natural poly phenol and have been established antioxidant effects in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…*Statistically significant compared to corresponding control at p < 0.001. potential, AA is a known neurotoxin (Tilson, 1981) and several occupationally exposed population studies have been reported to have an increased incidence of neurotoxicity syndromes (Deng et al, 1993) with typical symptoms of ataxia, skeletal muscle weakness, and weight loss (LoPachin, 2005). Similarly, neurotoxicity has also been reported in animal studies of AA-exposure, and is largely characterized by sensory, autonomic, and motor deficits due to nerve terminal dysfunction in the thalamus, basal ganglia, and other regions of the brain (Lehning et al, 2003;LoPachin, 2004LoPachin, , 2005Mehri et al, 2015). Indeed, we observed symptoms that resembled hind limb paralysis and sluggishness at 3 weeks of exposure to the high dose of AA; however, the symptoms associated with the likely neurotoxicity disappeared after cessation of AA-treatment and animals returned to phenotypic normal as soon as the AA treatment was stopped.…”
Section: Discussionmentioning
confidence: 99%